Non-Usury Business Model in Islamic Banking Practice (Waqf, Profit and Loss Sharing, Zakat) - Ismartono, Ismartono (Jurnal Manajemen, 2023)
One of the concepts that can be offered to solve the problem of the global economic crisis is the Islamic economic system, the application of which is integrated into the existing economic system. The Islamic Finance Institution in Indonesia has a great opportunity to be developed. Profit and Loss Sharing (PLS) can be used as an alternative solution to replace the interest system. The purpose of this study is to discuss the islamic banking practice model with capital from waqf, with PLS operational system, and followed with charity zakat activities. The writing methodology applied in this study is a descriptive method with a qualitative approach. The concept of the Islamic Bank model is found whose capital comes from productive waqf funds, so that the system can be full non-usury and its activities can be full ratio for profit and loss sharing (PLS). Savings are organized without interest (0%) and deposits with a profit-sharing ratio. Bank operations are taken from a small percentage of bank capital as a waqf fund manager. The bank's profits from business revenue sharing are partly regulated as zakat and the other part is for business development and situational reserves. It is necessary to think of Islamic economic experts to realize enabling conditions, in the form of supporting regulations, increasing the competence and professionalism of the nazir, as well as sufficient education/literacy. This paper can be a bridge to review Islamic banking practices in the future.